2021
DOI: 10.1109/access.2021.3105189
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Predict Laying Rate Based on Multiple Environment Variables

Abstract: Realizing an accurate laying rate prediction based on environmental factors plays a vital role in livestock and poultry breeding. In this paper, multiple environmental factors were considered to improve the accuracy of egg production rate prediction. A method was proposed by combining the Random Forest (RF) and Long Short-Term Memory (LSTM) to analyze the impact of the external environmental factors on the laying rate. Firstly, using RF, feature importance selection was implemented on environmental factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…This could be important for smaller farms that might not have multi-sensor equipment to measure various parameters that affect hen egg production (such as CO 2 , NH 3 ). A study carried out by [42] was aimed to determine the environmental factors that influence the egg production of laying waterfowls' (lion-head goose). The authors found that the optimal number of parameters was equal to four (i.e., laying rate, carbon dioxide, temperature, and dust) when forecasting, using a combination of LSTM and RF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be important for smaller farms that might not have multi-sensor equipment to measure various parameters that affect hen egg production (such as CO 2 , NH 3 ). A study carried out by [42] was aimed to determine the environmental factors that influence the egg production of laying waterfowls' (lion-head goose). The authors found that the optimal number of parameters was equal to four (i.e., laying rate, carbon dioxide, temperature, and dust) when forecasting, using a combination of LSTM and RF.…”
Section: Discussionmentioning
confidence: 99%
“…Long Short-Term Memory (LSTM)-is a model based on recurrent neural network that has been used in precision agriculture [41] and, regarding poultry industry, for laying rate prediction [42] as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation